The Role of Social and Technological Innovation in Enhancing Economic Well-being and Empowering Rural Communities - Amruddin; Suherlan; Suparwata, Dewa Oka (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Social and technological innovations have become key factors in addressing the challenges faced by rural communities, particularly regarding economic well-being and empowerment. This study aims to explore the role of social and technological innovations in improving the economic welfare and empowerment of rural communities. A literature review methodology with a qualitative descriptive analysis approach was employed. Data for this study were collected from Google Scholar, focusing on publications from 2018 to 2024. The study findings show that social and technological innovations play an important role in improving the economic welfare and empowerment of rural communities in Indonesia. Programmes such as ‘Tempe Producer Cooperative,’ ‘Digital Book,’ ‘Smart Village,’ ‘Bumdes,’ and ‘Telemedicine’ demonstrate that the application of innovative solutions can have a significant positive impact in improving the quality of life in rural areas. Through an approach that involves active community participation and appropriate use of technology, these initiatives are successfully addressing local problems, expanding access to services and information, and directly empowering communities. These programmes prove that the combination of social innovation and technology can drive sustainable and significant change in rural communities.